PENGARUH RASIO KEUANGAN TERHADAP RETURN SAHAM PADA PERUSAHAAN PUBLIK MANUFAKTUR - JULIA TRISCA; MUNGNIYATI MUNGNIYATI (Pusat Penelitian dan Pengabdian Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2017)
The purpose of this research is to obtain empirical evidence about the factor that effect the stock return among listed manufacturing companies in Indonesia Stock Exchanges. The factors are rate of return on sales, current ratio, asset turnover ratio, financial leverage, the proportion of profit margin before interest, tax and depreciation (EBITDM), working capital turnover, inventory turnover, the ratio of market value to book value of equity and earnings yield. Sample selection procedure carried out by implementing purposive sampling method. The samples of this research consist of 49 listed manufacturing company in Indonesia Stock Exchange during the period of 2011 – 2014. Hypothesis was tested used by multiple regression with SPSS program. The results of this research showed that rate of return on sales, asset turnover ratio, and earnings yield affected the stock return, while current ratio, financial leverage, the proportion of profit margin before interest, tax and depreciation (EBITDM), working capital turnover, inventory turnover, and the ratio of market value to book value of equity has no effect to stock return.